Lucky loser : how Donald Trump squandered his father's fortune and created the illusion of success - Buettner, Russ; Craig, Susanne (Penguin Press, 2024)
"Soon after announcing his first campaign for the US presidency, Donald J. Trump told a national television audience that life 'has not been easy for me. It has not been easy for me.' Building on a narrative he had been telling for decades, he spun a hardscrabble fable of how he parlayed a small loan from his father into a multi-billion-dollar business and real estate empire. This feat, he argued, made him singularly qualified to lead the country. None of it was true. Born to a rich father who made him the beneficiary of his own highly lucrative investments, Trump received the equivalent of more than $500 million today via means that required no business expertise whatsoever.Drawing on over twenty years' worth of Trump's confidential tax information, including the tax returns he tried to conceal, alongside business records and interviews with Trump insiders, New York Times investigative reporters Russ Buettner and Susanne Craig track Trump's financial rise and fall, and rise and fall again. For decades, he squanders his fortunes on money losing businesses, only to be saved yet again by financial serendipity. He tacks his name above the door of every building, while taking out huge loans he'll never repay. He obsesses over appearances, while ignoring threats to the bottom line and mounting costly lawsuits against city officials. He tarnishes the value of his name by allowing anyone with a big enough check to use it, and cheats the television producer who not only rescues him from bankruptcy but casts him as a business savant - the public image that will carry him to the White House. A masterpiece of narrative reporting, Lucky Loser is a meticulous, nearly-century spanning narrative, filled with scoops from Trump Tower, Mar-a-Lago, Atlantic City, and the set of The Apprentice. At a moment when Trump's tether to success and power is more precarious than ever, here for the first time is the definitive true accounting of Trump and his money - what he had, what he lost, and what he has left - and the final word on the myth of Trump, the self-made billionaire." --